Permanent Pacemaker Insertion in a Patient with Persistent Left Superior Vena Cava - Amit Gulati; Nivedita Calton; Cinosh Mathew; Rajneesh Calton (Wolters Kluwer Medknow Publications, 2022)
Implantation of a permanent pacemaker (PPM) in a patient with venous anomalies can be quite difficult, especially in a patient with persistent left superior vena cava (PLSVC). Our patient was a 63-year-old female who presented with complaints of dizziness and an episode of syncope. Her electrocardiogram was suggestive of a complete heart block. We approached the right side of the heart through the right infraclavicular cephalic vein initially, as that is the preferred site in our hospital. We encountered difficulty negotiating the leads through the right side, which raised the possibility of PLSVC. We report the various steps we took while inserting the PPM in this case.